Digital playgrounds : the hidden politics of children's online play spaces, virtual worlds, and connected games - Grimes, Sara M. author. (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
"Digital Playgrounds explores the key developments, trends, debates, and controversies that have shaped children's commercial digital play spaces over the past two decades. It argues that children's online playgrounds, virtual worlds, and connected games are much more than mere sources of fun and diversion - they serve as the sites of complex negotiations of power between children, parents, developers, politicians, and other actors with a stake in determining what, how, and where children's play unfolds. Through an innovative, transdisciplinary framework combining science and technology studies, critical communication studies, and children's cultural studies, Digital Playgrounds focuses on the contents and contexts of actual technological artefacts as a necessary entry point for understanding the meanings and politics of children's digital play. The discussion draws on several research studies on a wide range of digital playgrounds designed and marketed to children aged six to twelve years, revealing how various problematic tendencies prevent most digital play spaces from effectively supporting children's culture, rights, and - ironically - play. Digital Playgrounds lays the groundwork for a critical reconsideration of how existing approaches might be used in the development of new regulation, as well as best practices for the industries involved in making children's digital play spaces. In so doing, it argues that children's online play spaces be reimagined as a crucial new form of public sphere in which children's rights and digital citizenship must be prioritized."-- "Digital Playgrounds explores the key developments, trends, debates, and controversies that have shaped children's commercial digital play spaces over the past two decades. It argues that children's online playgrounds, virtual worlds, and connected games are much more than mere sources of fun and diversion - they serve as the sites of complex negotiations of power between children, parents, developers, politicians, and other actors with a stake in determining what, how, and where children's play unfolds. Through an innovative, transdisciplinary framework combining science and technology studies, critical communication studies, and children's cultural studies, Digital Playgrounds focuses on the contents and contexts of actual technological artefacts as a necessary entry point for understanding the meanings and politics of children's digital play. The discussion draws on several research studies on a wide range of digital playgrounds designed and marketed to children aged six to twelve years, revealing how various problematic tendencies prevent most digital play spaces from effectively supporting children's culture, rights, and - ironically - play. Digital Playgrounds lays the groundwork for a critical reconsideration of how existing approaches might be used in the development of new regulation, as well as best practices for the industries involved in making children's digital play spaces. In so doing, it argues that children's online play spaces be reimagined as a crucial new form of public sphere in which children's rights and digital citizenship must be prioritized."--